Producer’s willingness to adopt grassland carbon contracts in the southern plains - Sunderland, Isaac D. (Kansas State University, 2024)
The purpose of this paper is to quantify the willingness of farmers and ranchers within the Southern Great Plains to enter into agricultural carbon credit contracts on marginal grasslands, including as an alternative to the Conservation Reserve Program. A discrete choice experiment was conducted as part of a mail-in survey to agricultural producers in Kansas, Colorado, Oklahoma, Texas and New Mexico. The purpose of the discrete choice experiment was to assess the willingness of agricultural producers to enter into a carbon credit grassland contract as an alternative to the Conservation Reserve Program or as a value-added opportunity for marginal grasslands. Survey participants were asked to consider three independent choice scenarios with differing contract attributes. Contract options were composed of four attributes: (1) average annual payment per acre, (2) year-to-year payment variation, (3) ability to graze livestock, and (4) the length of the contract. To estimate the influence of the different attributes on the willingness of a producer to enter into a grassland conservation contract, we analyzed the stated choice experiment data using a mixed conditional logistic regression model. Survey data was collected during the summer of 2023 with 465 responses and a 12% response rate. The findings of this paper indicate that the average payment level per acre was an important contract attribute in the contract and that producers in the Southern Great Plains strongly value the ability to retain the ability to graze livestock on their marginal cropland when considering a grassland carbon credit contract. Producers also prefer a moderate 30% year-to-year variation in the prices that they receive in their carbon credit contracts.
Keywords: Carbon; Grasslands; Willingness to adopt